2012
DOI: 10.1111/apm.12020
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori free‐living and biofilm modes of growth: behavior in response to different culture media

Abstract: The physiological behavior of Helicobacter pylori in different growth conditions was investigated to approach its growth standardization. H. pylori free-living and biofilm modes of growth were assessed in four different liquid culture media (Brucella broth, brain heart infusion broth and Ham's F-12 supplemented with 2% fetal calf serum and Ham's F-12 without serum). Free-living growth was monitored during 72 h in each medium and characterized for bacterial density, culturability, viability and morphology. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…These results are in agreement with those obtained in the biomass quantification for the same experimental conditions. However, this result is not unexpected since there are several reports of the increase in biofilm formation in both Gram-positive and Gram-negative bacteria in the presence of sub-inhibitory concentrations of antibiotics [18,19,20]. Interestingly, the BIC value of aszonapyrone A ( 4a ) was found to be higher than 12× MIC against mature biofilms of both S. aureus B1 (BIC > 96 µg/mL) and E. faecalis W1 (BIC > 192 µg/mL).…”
Section: Resultsmentioning
confidence: 62%
“…These results are in agreement with those obtained in the biomass quantification for the same experimental conditions. However, this result is not unexpected since there are several reports of the increase in biofilm formation in both Gram-positive and Gram-negative bacteria in the presence of sub-inhibitory concentrations of antibiotics [18,19,20]. Interestingly, the BIC value of aszonapyrone A ( 4a ) was found to be higher than 12× MIC against mature biofilms of both S. aureus B1 (BIC > 96 µg/mL) and E. faecalis W1 (BIC > 192 µg/mL).…”
Section: Resultsmentioning
confidence: 62%
“…While it is unclear exactly what drives biofilm formation in H. pylori, protection from antibiotics and host defenses during infection (35,38,39) and/or protection in putative environmental reservoir (40-43) have been proposed. Basic characterization has shown that in vitro biofilm formation is varied across strains (32) and appears to be induced under conditions, such as serum/nutrient starvation (44,45). Initial investigations of the extracellular polymeric substances (EPS) matrix observed in in vitro biofilms revealed the presence of lipids, amino acids, and monosaccharides.…”
mentioning
confidence: 99%
“…The biofilm formation capacity was two-to three-fold better than in wild type strains with a functional luxS gene. The study investigating the effect of sub-MIC concentrations of antibiotics revealed the reduced expression of H. pylori luxS gene compared to the control bacteria not treated with antibiotic (20). These results suggest that there is an alternative way to control physiological changes in H. pylori exposed to environmental stress and that this system is associated with biofilm formation and conversion of bacteria to the coccoid form.…”
Section: H Pylori Morphological Formsmentioning
confidence: 88%